Effect Of Lantana Camara Plant Leaf Extracts On Black Soybean (Glycine soja L.) Plant Pests - Simanjuntak, Maria Phibertha; Wahyuni, Siti Hardianti; Dini Puspita Yanty (Jurnal Agricultural Science, 2024)
This study aims to determine the effect of leaf and flower extracts (Lantana camara) in controlling pod borers (Etiella zincknella) on black soybean (G. soja (L) Merril). This research was conducted in February-June 2024. The study used the non-factorial RAK (Randomized Group Design) method with treatments: PO = No treatment. P1 = Concentration of 5 grams of Lantana camara leaf extract /L. P2 = Concentration of 10 grams of Lantana camara leaf extract /L. P3 = Concentration of 15 grams of Lantana camara leaf extract /L. P4 = Concentration of 20 grams of Lantana camara leaf extract /L. P5 = Concentration of 25 grams of Lantana camara leaf extract /L. The parameters observed were: Plant height, number of leaves, weight of filled pods, percentage of attack. The treatment of Lantana camara leaf extract did not significantly affect the height, number of leaves and weight of pods of black soybean plants. In the percentage of treatment P0, P1, P2, P3 showed no significant difference to the percentage of black soybean pod sucking pest attack but the four treatments were significantly different from the P4 and P5 treatments.